Menilik Nasib Asuransi Syariah di Tengah Pandemi Covid-19 - Wahyuni Lely Augusna; Rozalinda Rozalinda; Ahmad Wira (UIN Imam Bonjol Padang, 2023)
The Covid-19 pandemic is called the “black-swan-effect” which has rocked the economy and the health sector. High mortality rates and a sluggish economy have made the financial industry's performance decline. This has become one of the factors in the decline in financial industry assets, namely the sharia insurance industry in Indonesia. The insurance industry should be ready to face the covid-19 pandemic because insurance companies have a lot of experience in dealing with unexpected events that impact society. This article describes an analysis of the development of Islamic insurance in Indonesia in the midst of the Covid-19 pandemic through asset and investment growth and identifies the factors that influence it. The approach to this study uses a qualitative research approach and the data used in this study is secondary data obtained through the official website of the Financial Services Authority in the form of insurance statistics for 2020 and IKNB data for 2020-2022. The results of this study indicate that there was a decline in sharia insurance assets and investments in Indonesia during the Covid-19 pandemic. This was due to economic pressure due to Covid-19 so that in general there was a decline in company performance. This finding can be a reference for Islamic insurance companies to have a special strategy when dealing with unexpected events that affect a large population of people.